ENHANCING LEARNING AUTONOMY: THE IMPACT OF CHATBOTS ON SELF-DIRECTED EDUCATION - Sain, Zohaib Hassan; Aziz, Aulia Luqman (Erudio Journal of Educational Innovation, 2025)
Self-directed learning (SDL) is a crucial approach to helping students develop their independence, adaptability, and lifelong learning mindset in a society that relies on rapidly changing information. It is becoming increasingly important for students to take charge of their own education as education systems shift towards more student-centered models. In this rapidly changing environment, robots powered by artificial intelligence (AI) have become game-changing tools that can transform how students learn and engage with information. Chatbots help students learn on their own or with personalized, engaging, and scalable help. They ensure that students receive feedback, inspiration, and adaptable learning experiences at the right time. The purpose of this study is to investigate how robots can assist individuals in learning independently in four key areas: setting goals and making plans, self-monitoring and metacognition, motivation and engagement, and customization through adaptable support. Based on well-known theories, such as Knowles' (1975) principles of self-directed learning and constructivist learning frameworks, this study suggests that robots can be utilized as digital learning teachers to help students learn independently and reflect on their learning process. Because they are intelligent and capable of engaging in conversations, robots help students set important goals, track their progress, and adjust their plans when they encounter problems. In the end, these systems provide students with the tools they need to build confidence, discover their own drive, and navigate their educational paths independently, which is transforming the way digital learning is conducted today.